2009
DOI: 10.1021/cm901757h
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Phase Analysis and Crystal Structure Investigation of a Bi1−xCaxFeO3−x/2 Perovskite-Related Solid Solution Phase and Selected Property Measurements Thereof

Abstract: A well-ordered, perovskite-related, Bi 1-x Ca x Fe III O 3-x/2 solid solution phase is synthesized via a rapid liquid phase sintering technique and shown to exist over the composition range ∼0.20 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 19 publications
(44 reference statements)
10
66
0
Order By: Relevance
“…One can see that compositional dependence of the lattice parameters in the rhombohedral phase deviates from a Vegard-type character expected for solid solutions (Fig. 2a) to be consistent with a complex structural state characteristic of the y = 0 samples [20,26,27]. Indeed, previous transmission electron microscopy measurements of this compound found a complicated behavior suggesting coexistence of the rhombohedral and two incommensurately modulated phases distinguished by the oxygen vacancies concentration [27].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…One can see that compositional dependence of the lattice parameters in the rhombohedral phase deviates from a Vegard-type character expected for solid solutions (Fig. 2a) to be consistent with a complex structural state characteristic of the y = 0 samples [20,26,27]. Indeed, previous transmission electron microscopy measurements of this compound found a complicated behavior suggesting coexistence of the rhombohedral and two incommensurately modulated phases distinguished by the oxygen vacancies concentration [27].…”
Section: Resultssupporting
confidence: 72%
“…1a). The parent compound, Bi 0.9 Ca 0.1-FeO 2.95 , was confirmed to exhibit a broadening of the Bragg peaks [19,20], which is supposed to be associated with a nanoscale coexistence of the competing structural phases near the ferroelectric-nonferroelectric phase boundary in the Bi 1-x Ca x FeO 3-x/2 system [26,27]. The broadening disappears upon Mn substitution (inset in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…5 Doping is known to modify the crystal structure and improve material properties: examples include La and K in PZT, [36][37][38][39] Sr and Ta in NaNbO 3 , [40][41][42][43] and Ca and Sm in BiFeO 3 . [44][45][46][47][48] Crystals of Mn-doped NBT have been reported to have: (i) enhanced resistivities, remnant polarizations, coercive fields, and d 33 values; (ii) a slight decrease in the phase transformation temperatures; and (iii) a decrease in the size of the T ferroelastic domains. 49 It is noted that the addition of Mn has little effect on the properties of NBT ceramics at room temperature, 50 which might indicate subtle differences between crystals and ceramics, possibly due to changes in stress accommodation of domains.…”
mentioning
confidence: 99%
“…One is with the help of leaching out the impurity by the diluted nitric acid [11]. Other research work involves the formation of solid solutions between the BiFeO 3 and other ABO 3 perovskites, or the Bi/Fe-site doping [12][13][14]. The alternatively method to obtain the pure BiFeO 3 phase is the complex solution processes, such as hydrothermal synthesis [15], sol-gel [16], and polymerized complex [17].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [6] has reported the rapid liquid phase sintering is effective way to obtain the BiFeO 3 ceramics with single phase and saturated ferroelectric polarization. Other research work proves that the formation of solid solutions between the BiFeO 3 and other ABO 3 perovskites, or the Bi/Fe-site doping can hinder the impurity phase formation and enhance the resistivity [12][13][14]. As for the Fe-site doping, Ti-doping has been reported to improve the synthesis and ferroelectricity of BiFeO 3 film or ceramics [7,12,20].…”
Section: Introductionmentioning
confidence: 99%